Agglutinated foraminifera from the Turonian–Coniacian boundary interval in Europe – paleoenvironmental remarks and stratigraphy - R. M. Besen; K. Schindler; A. S. Gale; A. S. Gale; U. Struck; U. Struck (Journal of Micropalaeontology, 2023)
Agglutinated foraminiferal assemblages of the Turonian–Coniacian from the GSSP (Global Boundary Stratotype Section and Point) of Salzgitter–Salder (Subhercynian Cretaceous Basin, Germany) and other sections, including Bielefeld–Ostwestfalendamm (Münsterland Cretaceous Basin, Germany) and the Dover–Langdon Stairs (Anglo-Paris Basin, England), from the temperate European shelf realm were studied in order to collect additional stratigraphic and paleoenvironmental information. Stable carbon isotopes were measured for the Bielefeld–Ostwestfalendamm section to establish a reliable stratigraphic correlation with other sections. Highly diverse agglutinated foraminiferal assemblages were obtained from sections in the German basins, whereas the fauna from Dover is less rich in taxa and less abundant. In the German basinal sections, a morphogroup analysis of agglutinated foraminifera and the calculated diversities imply normal marine settings and oligotrophic to mesotrophic bottom-water conditions. Furthermore, acmes of agglutinated foraminifera correlate between different sections and can be used for paleoenvironmental analysis. Three acmes of the species Ammolagena contorta are recorded for the Turonian–Coniacian (perplexus to lower striatoconcentricus zones, lower scupini Zone, and hannovrensis Zone) and likely imply a shift to more oligotrophic bottom-water conditions. In the upper scupini Zone below the Turonian–Coniacian boundary, an acme of Bulbobaculites problematicus likely indicates enhanced nutrient availability.